TROMBOSITOPENIA PADA PENGOBATAN DENGAN HEPARIN - B. Mulyadi,*; J. Soemarsono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Heparin induced thrombocytopenia (HIT), a well known side effect of heparin therapy, occurs in 1–5% of adults exposed to heparin.Unlike other drug induced thrombocytopenia, HIT does not usually cause bleeding, but instead cause thrombosis about 50% of HIT.The thrombosis in HIT can lead to limb gangrene or even death. The Importance to know the HIT is the wide use of heparin led tothe increasing recognition of untoward complications including HIT, relatively uncommon but severe side effect of heparin therapy,unpredictable, and difficulty in diagnosing and treating HIT. HIT is mediated by an antibody that recognizes an epitope on the plateletfactor (PF4)-heparin complex. The platelet factor (PF4)-heparin complex binds to FcgRII receptor on the platelet surface and crosslinksthereceptors.Thisinducesintenseplateletactivationandaggregationandsimultaneouslyactivatesbloodcoagulationpathways,thesechangesareprobablythebasisofthethrombosiseventsinHIT.HITwasclassifiedintotype1and2baseonthepathogenesisandtheseverityofHIT.RegularplateletcountmonitoringisbestsuitedforearlydiagnosisofHIT.Functional(serotoninrelease,plateletaggregationtest)andantigenassays(solidphaseenzymeimmunoassay,fluidphase,andparticlegelimmunoassay)areavailabletoconfirmHIT.HITwasmadebaseontheclinicalfindingandlaboratoryexamination.OnceHITisclinicallysuspected,heparinshouldbestoppedimmediatelyandtreatmentwithanalternativeanticoagulant,waitingforlaboratoryconfirmationmaybecatastrophic.Earlydiagnosisof HIT will decrease the morbidity and mortality.